2015
DOI: 10.4236/ojap.2015.44017
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Heavy Metals in Indoor Settled Harmattan Dust from the University of Agriculture Makurdi, Nigeria

Abstract: Indoor settled harmattan dusts at seven sampling stations from the University of Agriculture Makurdi were collected between November, 2014 to March, 2015 (five months) using the wipe sampling methodology. Gravimetric measurement of the dust samples from all the sample locations revealed that dust loading within the institution during the period of assessment ranges from 4.475 -6.533 g/m 2 . Masses of indoor settled dust were expectedly higher along high traffic, untarred roads and construction sites as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Moreover, to characterise the major metal components related the biochemical reactions, Ca, Mg, Na, K, Fe and P were determined in these bio-relevant fractions of household-dusts (Table 2). Similar with the potentially toxic metals, the levels of the major metal components were greater in the ALF fraction of household-dusts due to the acidic and complex environment of the solution compared to other tested bio-relevant solution (water, PSF, and Gamble's solution) and form of these major metals (e.g., oxide, chloride, carbonate) [42]. The highest concentration was determined at Fe in household-dusts extracted in water, ALF, and Gamble's solution compared to other major metals.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Moreover, to characterise the major metal components related the biochemical reactions, Ca, Mg, Na, K, Fe and P were determined in these bio-relevant fractions of household-dusts (Table 2). Similar with the potentially toxic metals, the levels of the major metal components were greater in the ALF fraction of household-dusts due to the acidic and complex environment of the solution compared to other tested bio-relevant solution (water, PSF, and Gamble's solution) and form of these major metals (e.g., oxide, chloride, carbonate) [42]. The highest concentration was determined at Fe in household-dusts extracted in water, ALF, and Gamble's solution compared to other major metals.…”
Section: Resultsmentioning
confidence: 92%
“…For example, metal oxides, carbonates, chlorides are known to be easily soluble in this media. This suggested these metals in household-dust can be form of oxides, carbonates, and chlorides rather than sul te, phosphate, and silico [42] (Innes et al 2021). However, there is no study to compare the ndings, and previous studies mostly conducted total amount of metals or using one physiological modelling.…”
Section: Resultsmentioning
confidence: 99%
“…Considering the wiping efficacy of tissue paper, herein, it was assumed that fine metal particles will be adhered (within the tissue surface) more than that of the bigger particles. 56 During performing the flowability test of the metal powders (with or without the PVP binder) using the flowmeter JIS-Z-2502, 57 the bound particles at different binder concentrations were found to be free-flowing compared to the non-bound particles. However, the flow rate did not change much (as shown in Figure 5c).…”
Section: Resultsmentioning
confidence: 99%
“…As a consequence of binding, it has been observed that the remaining metal dust adhered to the tissue surface was reduced after binding with PVP (as shown in Figure 5b). Considering the wiping efficacy of tissue paper, herein, it was assumed that fine metal particles will be adhered (within the tissue surface) more than that of the bigger particles 56 . During performing the flowability test of the metal powders (with or without the PVP binder) using the flowmeter JIS‐Z‐2502, 57 the bound particles at different binder concentrations were found to be free‐flowing compared to the non‐bound particles.…”
Section: Resultsmentioning
confidence: 99%
“…The concentrations of zinc were within these natural ranges and are significantly smaller than those reported in other studies. For example, a range of 4 -42 mg/kg was reported by Eneji et al (2015).…”
Section: Heavy Metal Concentration In Indoor Dustmentioning
confidence: 99%